Decentralized participatory plant breeding: a case from Syria - Ceccarelli, Salvatore; Grando, Stefania (International Development Research Centre, 2004)
Conventional modern plant breeding has been recognized to be more beneficial to farmers in high potential environments or those who could profitably modify their environment to suit new cultivars, than to the poorest farmers who could not afford to make the necessary modifications. As a consequence, low yields, crop failures, malnutrition and poverty affect a large proportion of humanity.